Sufism Values in Pancasila as the Nation's Ideology - Abid Nurhuda (Athena: Journal of Social, Culture and Society, 2023)
Indonesia was born on August 17, 1945, at the same time as the emergence of the term Pancasila which is composed of existing cultural values, personality, statehood, and societal norms so that it becomes the Ideology of the Nation. The ideology is actual, dynamic, and open so that it allows for new innovative thoughts, one of which is the teachings of Sufism which are used as a shield to answer the current moral decline. So the purpose of this study is to describe the values of Sufism in Pancasila as the National Ideology. The method used is descriptive qualitative with a literature study approach, collecting data using documentation techniques and careful observation of each data. Then analyzed the relevant contents and finally concluded. The results of the study show that the values of Sufism in Pancasila as the National Ideology include Takhalli which is manifested in the first precept as a form of conformity of human nature to be empty of disgraceful attitudes that do not exist in God by drawing closer to him. Then Taḥalli which is manifested in the second, third, and fourth precepts as a form of human self-decoration through a just, civilized attitude, united with a spirit of cooperation and wise deliberation. And finally is Tajalli which is manifested in the fifth precept as a form of application of the divine nature in humans daily so that all-around justice is felt